Contrast-Enhanced Ultrasound (CEUS) in Hepatic Lymphoma: Retrospective Evaluation in 38 Cases - Trenker, C.; Kunsch, S.; Michl, P.; Wissniowski, T. T.; Goerg, K.; Goerg, C. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Purpose: Description of contrast-enhanced ultrasound (CEUS) patterns of hepatic lymphoma.Materials and Methods: Over a period of 6 years and 1 month from January 2006 to January 2012, n = 38 patients with histological or clinically apparent hepatic lymphoma were studied by means of CEUS prior to B-mode imaging.Results: Using B-mode imaging, lesions were hypoechoic in n = 37 (97.4 %) cases, while a focal lymphoma lesion was echo-rich in 1 case (2.6 %). For comparison, with CEUS, a hyperenhanced signal during the arterial phase was observed in n = 9 (23.7 %), an isoenhanced signal in n = 17 (44.7 %) and a hypoenhanced signal in n = 12 (31.6 %) cases. During the portal phase n = 2 (5.3 %) lesions were isoenhanced and n = 36 (94.7 %) were hypoenhanced followed by a hypoenhancement in n = 38 (100 %) cases in the late phase.Conclusion: Lymphomas of the liver can cause different contrast accumulation in the arterial phase of CEUS. Furthermore, a clear differentiation from other malignant liver lesions such as metastases is crucial as different contrast accumulation in the arterial phase of CEUS is observed. In the late phase, hepatic lymphomas lead to a hypoenhancement in CEUS, also known as a “wash-out” phenomenon. In conclusion, CEUS is helpful to differentiate hepatic lesions by means of evaluating the malignancy or benignancy. In this regard, the application of CEUS can help to find the right diagnosis. A final discrimination between malignant liver lesions, such as liver lymphomas, metastasis or HCC, remains impossible.
Keywords: CEUS; liver; lymphoma; oncology